2008
DOI: 10.1111/j.1460-9568.2008.06349.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced long‐term potentiation and impaired learning in phosphodiesterase 4D‐knockout (PDE4D−/−) mice

Abstract: Elevation of intracellular cyclic adenosine monophosphate (cAMP) concentrations and subsequent regulation of downstream target gene expression through phosphorylation of cAMP-responsive element binding protein (CREB) is hypothesized to underlie the mechanism(s) of long-term memory (LTM) formation. The phosphodiesterase 4 (PDE4) enzyme family is believed to play a key role in LTM by regulating cAMP levels. Thus far, four PDE4 isoforms have been identified (PDE4A, B, C and D); however, the requisite involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 48 publications
2
77
1
Order By: Relevance
“…Although generally increased hippocampal LTP correlates with improved learning and memory, pathological and prolonged increase in LTP may also lead to cognitive defects (50)(51)(52)(53)(54). The perseveration that we observed could indicate an effect of Nogo-A knockdown on memory, which is currently being analyzed in more detail.…”
Section: Discussionmentioning
confidence: 70%
“…Although generally increased hippocampal LTP correlates with improved learning and memory, pathological and prolonged increase in LTP may also lead to cognitive defects (50)(51)(52)(53)(54). The perseveration that we observed could indicate an effect of Nogo-A knockdown on memory, which is currently being analyzed in more detail.…”
Section: Discussionmentioning
confidence: 70%
“…Evidence has demonstrated that ␤-arrestins can form stable complexes with PDE-4s in the desensitization system independent of agonist treatment (31). Behavior experiment also implicated the role of PDE-4, especially PDE-4D, in amygdala-dependent fear conditioning responses (32,33,38). Although ␤-arrestin-2 is ubiquitously expressed in CNS, Arrb2 Ϫ/Ϫ mice exhibit impaired fear conditioning and normal Morris water maze.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also investigated the PDE-4 subtypes such as PDE-4 A, B and D (Houslay and Milligan, 1997), which are distributed throughout the brain (Perez-Torres et al, 2000;Bian et al, 2004), Specifically, PDE-4 A is highly expressed in rat hippocampus CA1 sub-region ; PDE-4B is predominantly present in the amygdala, hypothalamus, striatum, frontal cortex and olfactory bulb as well as hippocampus (Dlaboga et al, 2006;Zhang et al, 2008); PDE-4 C is minimally expressed in the CNS ; PDE-4D is expressed in hippocampal CA1 region (Zhang et al, 2002;Rutten et al, 2008b). All these subtypes are selective for cAMP (Rutter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%